Intervensi Faktor Sensitif Dan Spesifik Dalam Upaya Pencegahan Anak Balita Kegemukan Dan Obesitas Di Kelurahan Karanganyar Kota Tangerang - Titus Priyo Harjatmo; Anastu Regita Naweswara; Ani Noviani (CV. Multi Kreasi Media, 2025)
The prevalence of overweight and obesity in children is increasing. The prevalence of childhood obesity has increased in various countries, including Indonesia. Based on data from the 2018 Basic Health Research, the prevalence of obesity in children aged 5-12 years is still high, namely 18.8% consisting of obese 10.8% and very obese (obese) 8.8%. Obesity in children will become a health problem such as diabetes, high blood pressure, and cholesterol. Excess fat that accumulates in the body causes various health problems such as diabetes, dyslipidemia, cardiovascular and cancer which will reduce a person's quality of life. As a result of obesity in the cardiovascular system, the heart pumps blood, which is carried back and forth between the heart and body by blood vessels. Arteries, which move blood from the heart to the rest of the body, are not just simple tubes, but a series of dynamic channels that control blood flow. Obesity in children in particular will be a problem because the extra weight the child has will eventually lead to health problems that are usually experienced by adults such as diabetes, high blood pressure, and cholesterol. Community service activities were carried out in Karanganyar Village, Tangerang City, targeting 15 participants who have toddlers with overweight and obesity nutritional status. After the community service activities were carried out, there was an increase in knowledge about growth monitoring, feeding toddlers and clean and healthy living behavior.